Case for diagnosis. Verrucous plaque on the pubic region, - Diego Henrique Morais Silva; Anna Karoline Gouveia de Oliveira; Neusa Yuriko Sakai Valente; Thais do Amaral Carneiro Cunha (Sociedade Brasileira de Dermatologia, 2021)
Abstract Muir-Torre syndrome is a rare, autosomal dominant genodermatosis, characterized by sebaceous neoplasms and visceral carcinomas. The authors describe the case of a patient who, 16 years after the diagnosis of colon carcinoma, presented a verrucous plaque on the pubic region, histopathologically compatible with sebaceous adenoma. The need to investigate this syndrome is emphasized, especially in cases of sebaceous neoplasms located outside the head, face, and neck. Screening for neoplasms in these patients and their families is mandatory.